Alterations of DNA methylation during adipogenesis differentiation of mesenchymal stem cells isolated from adipose tissue of patients with obesity is associated with type 2 diabetes - Elaheh Mirzaeicheshmeh (Taylor & Francis Group, 2021)
Adipogenesis regulation is crucial for mature adipocyte function. In obesity, a major driver of type 2 diabetes (T2D), this process is disrupted and remains poorly characterized. Here we identified altered DNA methylation profiles in diabetic obese patients, during three adipocytes differentiation stages. We isolated mesenchymal cells from visceral adipose tissue of obese patients with and without T2D to analyse DNA methylation profiles at 0, 3, and 18 days of ex vivo differentiation and documented their impact on gene expression. Methylation and gene expression were analysed with EPIC and Clarion S arrays, respectively. Patients with T2D had epigenetic alterations in all the analysed stages, and these were mainly observed in genes important in adipogenesis, insulin resistance, cell death programming, and immune effector processes. Importantly, at 3 days, we found six-fold more methylated CpG alterations than in the other stages. This is the first study to document epigenetic markers that persist through all three adipogenesis stages and their impact on gene expression, which could be a cellular metabolic memory involved in T2D. Our data provided evidence that, throughout the adipogenesis process, alterations occur in methylation that might impact mature adipocyte function, cause tissue malfunction, and potentially, lead to the development of T2D.